Facteurs de satisfaction associés au bonheur de l’adulte - Laroche, Christiane; de Grâce, Gaston-René (Canadian Journal of Counselling and Psychotherapy, 2007)
Over the past twenty years, numerous articles on the factors of satisfaction associated with happiness in adults have been published. Approximately forty of these studies seem of particular importance and can be categorized according to the following themes: personality; emotions; interpersonal relationships; social activities and leisure; work; educational level, socio-economic status and income; age; and gender. This article first presents a critical review of this literature. Beyond facilitating a better understanding of the relative contribution of each factor associated with happiness, this review makes suggestions for methodology and presents avenues for future research. It also offers applications which could be of use to professionals either in personal growth or the therapeutic context.